Aspen Plus Simulation-based Thermodynamic Assessment of Multistage Coffee Oil Extraction from Arabica Spent Coffee Ground - Amani Salsabil Husodo; Nur Ikhtiarini; Yuyun Yuniati; Moh. Ainul Fais (Journal of Chemical Process Engineering, 2026)
The potential source of lipid material is spent coffee grounds (SCG). However, simultaneously, polar co-compounds (e.g., caffeine, chlorogenic acid, and cafestol) can be leached using ethanol-based processing, which must be separated in stages. The article is a thermodynamic study on an equilibrium-based multistage coffee-oil separation flowsheet with ethanol solvent (treated as 96 %(w/w) ethanol in this study) and a dry-basis definition of the feed. The flowsheet was adjusted to represent a sequential mixer-separator with solids proceeding stage-to-stage and fresh solvent contacts, with the first and second stages intended to demonstrate the leaching process, and the rest performed the purification process. Stagewise results indicate that cumulative elimination of the three monitored polar compounds is over 97% at Stage 3 and over 99.9% at Stage 4, and there is a plateau in the impurity removal; additionally, Stage 5 provides only slight further elimination. At the fifth level, oil recovery drops beyond the 69% (S/F 1:1, 40 C) to 58 (S/F 5:1, 60 °C), where an equilibrium-based trade-off between separation ability and lipid retention is shown. Varying binary interaction parameters (BIP) by 10% values resulted in slight alterations of recovery and never affected the qualitative stagewise inferences. Since this work is only done with the simulations of equilibrium, all the performance values are to be understood as the thermodynamic tendencies and the upper-bound signal; engineering design is to be suggested with an explicit experiment and with the separation/solvent-recovery studies on the laboratory level.